Proses Pemberadaban Membatik Pada Perempuan Sebagai Modal Budaya bagi Pembatik Madura, Desa Tanjungbumi, Bangkalan - Syarifudin, Achmad; Hidayati, Sri; Andriani, Anik (Postgraduate, University of Mataram, 2024)
Batik has become a cultural identity for Indonesian people. Madura Island also has cultural richness in the form of Madurese batik which is still preserved to this day, inseparable from the batik civilization of Tanjungbumi Village, Bangkalan Regency. This research is aim to identify the process of civilizing process of women's batik as the cultural capital of Madurese batik craftsmen in Tanjungbumi Village. This research conducted in Tanjungbumi Village in August 2023. The research method used qualitative research. Techniques through observation and interviews with purposive sampling. This research is very important and useful for stakeholders in formulating policies for developing the Madurese batik business in Tanjungbumi Village, Bangkalan Regency. The results of the study shows that the process of civilizing process of batik according to Norbert Elias can take place through two processes, namely psychogenesis and sociogenesis. First, psychogenesis can be understood through batik techniques that have been passed down from generation to generation by families. The philosophical meaning of batik as basic knowledge through the family is then internalized by batik makers in producing batik. The value of tenacity and patience inherent in women as part of the sociogenesis of batik making needs to be owned and produced repeatedly. Second, sociogenesis takes place as a reinforcement of the social construction that women are still synonymous with batik. Third, this civilization process will become cultural capital that can be maintained, including through the social institutions of the family, batik community and government through batik development training in Tanjungbumi Village, Bangkalan